Caregiver perceptions of usual care home programs for persons with acquired brain injury: a qualitative descriptive study - Donoso Brown, Elena V.; Stepansky, Kasey; Wallace, Sarah E.; Bien, Isabella; Buttino, Emma (Frontiers in Rehabilitation Sciences, 2025)
ObjectiveThe study explores caregiver perceptions of home programs for clients with acquired brain injury based on current clinical care after transition to the community.DesignA qualitative descriptive study.SettingWithin the community, post inpatient rehabilitation.ParticipantsA convenience sample of eight caregivers of clients with acquired brain injury from one clinical site. All participants spoke English, were between the ages of 18 and 85 years, had no neurodegenerative disorders, and self-identified as caregivers.ProceduresTwo nested semi-structured interviews were completed post-discharge from an inpatient rehabilitation facility. All interviews were audio recorded and transcribed. Qualitative data analysis was performed utilizing MAXQDA© software, consensus coding, and abstraction of themes.ResultsTwo themes with subsequent subthemes were identified: (1) Systems, Roles, and Responsibilities Influenced Caregivers' Perceptions of Home Program and Recovery Outlook and (2) Caregivers' Home Program Experience. The first theme addresses topics of caregiver roles and responsibilities, system supports and barriers, and their general outlook on recovery. Within the second theme, results provide a chronological description of home program training, use, and modification.ConclusionsA caregiver’s outlook on the care receiver’s recovery and home program implementation is influenced by the burden of responsibilities, and system-level supports and barriers. The home program experience of the caregivers was reported to involve limited but satisfactory training. Caregivers saw the value in home programs and advised others to engage in them. Future programs should encourage healthcare providers to provide explicit instruction to the caregiver about their intrinsic value to home program implementation and adherence.